Short Communication: Genetic variation of Coelogyne pandurate, C. rumphii and their hybrids based on RAPD markers - Sri Hartati; ENDANG S. MULIAWATI (Society for Indonesian Biodiversity, 2020)
Abstract. Hartati S, Muliawati ES. 2020. Short Communication: Genetic variation of Coelogyne pandurata, C. rumphii and their hybrids based on RAPD markers. Biodiversitas 21: 4709-4713. One effort to increase the genetic diversity of orchids is by crossing. This research aims to assess the genetic variation of a hybrid orchid obtained by crossing Coelogyne pandurata and C. rumphii and their hybrids based on RAPD markers. In this research, both parents were analyzed in three replications, while the hybrid was done in 10 replications. The study was conducted by analyzing DNA bands using RAPD markers with six primers, i.e. OPA 02, OPA 07, OPA 13, OPB 12, OPB 17, and OPD 08. Identification of the parents and their F1 hybrids showed 95.83% polymorphic bands with 43 bands measuring 200-2100 bp. The parents of C. rumphii, C. pandurata, and their hybrids showed similarity range of 0.16-1.00. The crossing of C. rumphii and C. pandurata resulted in a similarity of 0.5, shown in two large clusters. The first cluster consisted only of C. pandurata males and the second cluster consisted of C. rumphii females, together with all hybrid individuals. This study succeeded in creating new hybrids of orchids that have different characters from their parents, having a genetic variation of 23%.